Photoresponsive frameworks: energy transfer in the spotlight. (2nd July 2021) - Martin, Corey R.; Park, Kyoung Chul; Corkill, Ryan E.; Kittikhunnatham, Preecha; Leith, Gabrielle A.; Mathur, Abhijai; Abiodun, Sakiru L.; Greytak, Andrew B.; Shustova, Natalia B.
Abstract : Photochromic units integrated within metal- and covalent-organic framework matrices act as a switch to control resonance energy transfer processes. Abstract : In this paper, spiropyran-containing metal- and covalent-organic frameworks (MOFs and COFs, respectively) are probed as platforms for fostering photochromic behavior in solid-state materials, while simultaneously promoting directional energy transfer (ET). In particular, Förster resonance energy transfer (FRET) between spiropyran and porphyrin derivatives integrated as linkers in the framework matrix is discussed. The photochromic spiropyran derivatives allow for control over material optoelectronic properties through alternation of excitation wavelengths. Photoinduced changes in the material electronic profile have also been probed through conductivity measurements. Time-resolved photoluminescence studies were employed to evaluate the effect of photochromic linkers on material photophysics. Furthermore, "forward" and "reverse" FRET processes occurring between two distinct chromophores were modeled, and the Förster critical radii and ET rates were estimated to support the experimentally observed changes in material photoluminescence.